Study on the shear performance of adhesive shear connectors in push-out tests. (August 2021) - Zhan, Yulin; Duan, Mengjun; Zhang, Lei; Liu, Chudong; Li, Zhaoyu; Zhao, Renda
Abstract: This paper introduces the adhesive shear connector aiming to remedy the defects of traditional mechanical shear connectors, such as stress concentration, discontinuous shear stress transmission and welding residual stress. To study the shear behavior of such connectors, the push-out tests of two groups of adhesive shear connector specimens (6 in total) were designed and completed, in which the adhesive materials are epoxy resin and magnesium phosphate cement (MPC) respectively. During the whole process of loading, the stress–strain curve, stress-slip curve and failure modes were obtained. In addition, the calculation method of predicting the ultimate shear bearing capacity of adhesive shear connectors was also explored. The results show that the shear strength of epoxy resin shear connector is higher than that of MPC one. The average shear strength of epoxy resin shear connectors is about 4.07 MPa, which is higher than that of the traditional stud shear connectors which is 3.0 MPa, indicating that epoxy resin shear connectors have the same interface shear capacity as traditional stud shear connectors. The failure mode of epoxy resin shear connectors is mainly the strength failure of concrete or adhesive layer, while the failure mode of MPC shear connectors is mainly the debonding failure between binder and steel. Suggestion for further study is that metal shear connectors can be used in combination with the adhesive shear connectors so as to make full use of the advantages of both.